Rozwiązane

doprowadz kazde z rownan do najprostrzej postaci i rozwiążuklad rownan metoda podtstawiania.
{x-3(y-3x)=3x-4
{2(2x-y)=4



Odpowiedź :

[tex]\\\begin{cases}x-3y+9x=3x-4\\ 2(2x-y)=4 /:2\end{cases} \\\begin{cases}10x-3x-3y=-4\\2x-y=2\implies y=2x-2 \end{cases} \\7x-3(2x-2)=-4 \\7x-6x+6=-4 \\x=-4-6=-10 \\y=2*(-10)-2=-22 \\Odp. \begin{cases}x=-10\\y=-22\end{cases}[/tex]

 

x - 3(y - 3x) = 3x - 4

2(2x - y) = 4  /:2

 

x - 3y + 9x = 3x - 4

2x - y = 2

 

10x - 3x - 3y = -4

2x - y = 2

 

7x - 3y = -4

y = 2x - 2

 

7x - 3(2x - 2) = -4

7x - 6x + 6 = -4

x = -4 -6

x = -10

---------

y = 2*(-10) -2

y = -22

----------

 

{x = -10}

{y = -22}